2008
DOI: 10.1179/174328108x287928
|View full text |Cite
|
Sign up to set email alerts
|

Influence of raw material particle size on quality of pellets

Abstract: Pellet plant (4?2 MPta capacity) of JSW Steel Ltd imports iron ore fines from different mines to produce pellets for its Corex and Blast Furnace plants. The pelletisation process involves drying the ore fines to reduce the moisture content to less than 1%, grinding in open circuit ball mills to get required fineness. To produce good quality of pellets certain additives are important and limestone is employed for modifying the pellet basicity. Iron ore fines of 210 mm size and limestone are ground together in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
(8 reference statements)
1
12
0
1
Order By: Relevance
“…This may be due to the higher amount of closed pores formation during induration in high basicity region. Umadevi et al 18) reported that CaCO 3 in limestone particle in pellet decomposed to CaO and CO 2 gas. Then the produced porous and cracked CaO is dissolved by forming Calcium ferrite, SCA or SFCA phases leaving a pore on that place.…”
Section: Effect Of Basicitymentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the higher amount of closed pores formation during induration in high basicity region. Umadevi et al 18) reported that CaCO 3 in limestone particle in pellet decomposed to CaO and CO 2 gas. Then the produced porous and cracked CaO is dissolved by forming Calcium ferrite, SCA or SFCA phases leaving a pore on that place.…”
Section: Effect Of Basicitymentioning
confidence: 99%
“…The swelling index is slightly higher in 0.8 basicity than 0.25 basicity. One more problem with high basicity is the crack formation Umadevi et al 18) has found in high basicity pellets that the conversion of glass phase to the crystallized wllastonite phase happens during reduction at around 800-900°C and during conversion, cracks forms over the entire pellet. This may also be the reason of comparatively higher swelling index in 0.8 basicity pellets (i.e high CaO content).…”
Section: Effect Of Basicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although, investigators (Onoda et al 1980;Dwarapudi et al 2011;Umadevi et al 2011) have studied on quality improvement of hematite pellet by addition of fluxes or carbon, a study on pellet properties with the fineness of hematite ore fines is also imperative. The effect of iron ore fine size on pellet properties has recently been studied by several investigators (Umadevi et al 2008;Pal et al 2009;Dwarapudi et al 2010;Dwarapudi et al 2011). They, however, studied the effect of ore size as per its sieve analysis in terms of mesh size or diameter in ''mm.''…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, The characterization of the particle size and the surface features of iron ores is of vital importance for the studies of mineral processing. [2][3][4][5][6][7] The specific surface area of iron ore particles can be measured by nitrogen adsorption, laser diffraction, and mathematical models based on the size distribution. 8) However, what is the difference among these methods and what is the indication of the results were less discussed on the iron ore granulation, which is the right topic of the present study.…”
Section: Introductionmentioning
confidence: 99%